A midgut lysate of the Riptortus pedestris has antibacterial activity against LPS O-antigen-deficient Burkholderia mutants. (February 2017) - Jang, Ho Am; Seo, Eun Sil; Seong, Min Young; Lee, Bok Luel
Abstract: Riptortus pedestris, a common pest in soybean fields, harbors a symbiont Burkholderia in a specialized posterior midgut region of insects. Every generation of second nymphs acquires new Burkholderia cells from the environment. We compared in vitro cultured Burkholderia with newly in vivo colonized Burkholderia in the host midgut using biochemical approaches. The bacterial cell envelope of in vitro cultured and in vivo Burkholderia differed in structure, as in vivo bacteria lacked lipopolysaccharide (LPS) O-antigen. The LPS O-antigen deficient bacteria had a reduced colonization rate in the host midgut compared with that of the wild-type Burkholderia . To determine why LPS O-antigen-deficient bacteria are less able to colonize the host midgut, we examined in vitro survival rates of three LPS O-antigen-deficient Burkholderia mutants and lysates of five different midgut regions. The LPS O-antigen-deficient mutants were highly susceptible when cultured with the lysate of a specific first midgut region (M1), indicating that the M1 lysate contains unidentified substance(s) capable of killing LPS O-antigen-deficient mutants. We identified a 17 kDa protein from the M1 lysate, which was enriched in the active fractions. The N-terminal sequence of the protein was determined to be a soybean Kunitz-type trypsin inhibitor. These data suggest that the 17 kDa protein, which was originated from a main soybean source of the R. pedestris host, has antibacterial activity against the LPS O-antigen deficient (rough-type) Burkholderia. Highlights: Burkholderia LPS O-antigen-deficient bacteria had a reduced colonization rate in the host midgut. In vitro survival rates of three LPS O-antigen-deficient mutants were examined. A specific midgut contains substance killing LPS O-antigen-deficient mutants. 17 kDa trypsin inhibitor has antibacterial activity against the LPS O-antigen-deficient mutant.